Tremulatory and Abdomen Vibration Signals Enable Communication through Air in the Stink Bug Euschistus heros - Kavčič, Andreja (Public Library of Science, 2013)

(untitled)
Communication by substrate-borne mechanical signals is widespread among animals but remains one of their least understood communication channels. Past studies of vibrational communication in insects have been oriented predominantly to communication during mating, showing that species- and sex-specific vibrational signals enable recognition and localization of potential mates on continuous solid substrates. No special attention has been paid to vibrational signals with less obvious specificity as well as to the possibility of vibrational communication across substrates that are not in physical contact. We aimed to reinvestigate emission of the aforementioned vibrational signals transmitted through a plant in the stink bug Euschistus heros (Pentatomidae: Pentatominae) and to check whether individuals are able to communicate across adjecent, physically separated substrates. We used laser vibrometry for registration of substrate-borne vibrational signals on a bean plant. Using two bean plants separated for 3 to 7 cm between two most adjacent leaves, we investigated the possibility of transmission of these signals through air. Our study showed that males and females of E. heros communicate using tremulatory, percussion and buzzing signals in addition to the previously described signals produced by vibrations of the abdomen. Contrary to the latter, the first three signal types did not differ between sexes or between pentatomid species. Experiments with two physically separated plants showed significant searching behaviour and localization of vibrational signals of an E. heros male or a female, in response to abdominal vibration produced signals of a pair duetting on the neighbouring plant, in comparison to control where no animals were on the neighbouring plant. We also confirmed that transmission through air causes amplitude and frequency decay of vibrational signals, which suggests high-amplitude, low-frequency tremulatory signals of these stink bugs their most plausible way of communication across discontinuous substrates.